VvBAP1, a Grape C2 Domain Protein, Plays a Positive Regulatory Role Under Heat Stress - Ye, Qing; Yu, Jintao; Zhang, Zhen; Hou, Lixia; Liu, Xin (Frontiers in Plant Science, 2020)
High temperature is one of the main abiotic stresses that threatens plant growth and development. Grapevine is one of the most economically important plants, and the production and quality of grapevine are often affected by some extreme climatic conditions, especially heat stress. However, the mechanisms of the response and adaptation of grapevine to heat stress are not well understood. Previously, we showed that a BON association protein from grapevine, VvBAP1, has a positive effect on cold tolerance. In the present study, we further explored the underlying physiological and molecular mechanisms of VvBAP1 in response to heat stress. The results indicated VvBAP1 was significantly induced by high temperature, and the expression of VvBAP1 in the resistant grapevine varieties was significantly higher than sensitive varieties. Overexpression of VvBAP1 in Arabidopsis significantly promoted the germination and growth of transgenic plants under heat stress, indicating that VvBAP1 has a positive role in the heat resistance. The chlorophyll content and net photosynthetic rate in the transgenic Arabidopsis was significantly higher than wild type. Overexpression of VvBAP1 also enhanced antioxidant enzymes activity and contributed to increase the expression of antioxidant enzyme genes, that to reduce the accumulation of reactive oxygen species and the lipid peroxidation under heat stress. In addition, the transcriptional activities of several heat stress response genes were increased in transgenic plants. In summary, we propose that VvBAP1 may play a potential important role in resistance against heat stress in grapevine, primarily through a combination of enhanced antioxidant activity and increased heat stress response genes expression.